2015
DOI: 10.1037/tra0000047
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of wantedness and consent during nonconsensual sex: Implications for posttraumatic cognitions.

Abstract: Social-cognitive models of traumatic stress have urged researchers to investigate the complex changes in victims' systems of belief following trauma. Among victims of rape, posttraumatic cognitions related to self-blame, safety, trust, intimacy, control, power, and esteem are common negative outcomes; yet there is great variability in the degree to which rape victims exhibit these reactions, and this remains unexplained. Two possible factors that may be relevant to the development of these posttraumatic cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Participants often suggested that a non-consensual scenario was consensual because it was wanted and, similarly, suggested that a consensual scenario could have been non-consensual because it was not wanted. Responses may reflect previous research findings that suggest wantedness and consent can be rated as synonymous and also contrasting concepts (Artime and Peterson, 2015) which may suggest a lack of understanding in public perceptions of consent. Participant responses seem to represent wanting from the victim rather than the perpetrator in which, if the victim wanted to have sex, then the person has consented to it.…”
Section: Attractivenessmentioning
confidence: 62%
“…Participants often suggested that a non-consensual scenario was consensual because it was wanted and, similarly, suggested that a consensual scenario could have been non-consensual because it was not wanted. Responses may reflect previous research findings that suggest wantedness and consent can be rated as synonymous and also contrasting concepts (Artime and Peterson, 2015) which may suggest a lack of understanding in public perceptions of consent. Participant responses seem to represent wanting from the victim rather than the perpetrator in which, if the victim wanted to have sex, then the person has consented to it.…”
Section: Attractivenessmentioning
confidence: 62%
“…Foa and Rothbaum (1998) suggested that negative cognitions about the self are characteristic for victims of sexual violence. It has been demonstrated that self-blame also plays important role in the processing of sexual violence (Halligan et al 2003;Dunmore et al 2001;Artime and Peterson 2015;Steine et al 2017). The current study differentiated between women who had experienced sexual abuse and women who had been exposed to other types of trauma.…”
mentioning
confidence: 80%
“…Cognitive models of the psychological reaction to trauma are based on the assumption that the subjective appraisal of an event has effect on the response to trauma and the severity of trauma related symptoms (Ehlers and Clark 2000); and that negative posttraumatic cognitions mediate the relationship between exposure to trauma and psychopathology. There is vast evidence suggesting that individuals exposed to trauma often develop negative beliefs about themselves and the world (Foa and Riggs 1993;Foa and Rothbaum 1998;Artime and Peterson 2015)this seems to apply mostly to individuals who lack social support and personal resources to deal with trauma (Zang et al 2017). Holding negative views about oneself is, in turn, associated with higher severity of psychiatric symptoms related to traumasuch as posttraumatic stress disorder or generalized anxiety disorder (Samuelson et al 2016;Beck et al 2015).…”
mentioning
confidence: 99%
“…It may also have negative social consequences such as the normalization of sexual abuse. But some evidence suggests that not defining the experience as sexual abuse may also protect against posttraumatic emotions and cognitions associated with self-blame and lower self-esteem (Artime and Peterson 2015). One reason for this may be that individuals who perceive the experience as unwanted and nonconsensual are more likely to demonstrate self-blame (Artime and Peterson 2015).…”
mentioning
confidence: 99%
“…But some evidence suggests that not defining the experience as sexual abuse may also protect against posttraumatic emotions and cognitions associated with self-blame and lower self-esteem (Artime and Peterson 2015). One reason for this may be that individuals who perceive the experience as unwanted and nonconsensual are more likely to demonstrate self-blame (Artime and Peterson 2015). However, some studies suggested that individuals struggling to define their experience display similar or worse psychological and emotional difficulties compared to individuals who acknowledged their negative experience as sexual abuse (Frazier and Seales 1997;Marx and Soler-Baillo 2005).…”
mentioning
confidence: 99%